Corporate governance mechanisms, royal family ownership and corporate performance: evidence in gulf cooperation council (GCC) market - Omar Ikbal Tawfik; Ahnaf Ali Alsmady; Rashidah Abdul Rahman; Maha Faisal Alsayegh (Heliyon, 2022)
This research is motivated by the increasing importance of the Gulf Cooperation Council (GCC) economies within the world economy and the lack of research on corporate governance mechanisms in these countries. This study examines the relationship between corporate governance mechanisms and firm performance in GCC countries, focusing on the uniqueness of royal family ownership. We further investigate whether corporate governance mechanisms affect the royal family ownership–firm performance relationship. The data sample of the study includes 266 company-year observations over the period of 2009–2017. Results demonstrate that board size with less than nine members on board and audit quality (AUQ) are effective corporate governance mechanisms because their monitoring functions can enhance firm performance. However, our result demonstrates that firm performance significantly deteriorates with institutional ownership, chief executive officer duality (CEODU) and local auditors (AUQL). The result also shows that royal ownership has a significant positive effect on firm performance. In line with the resource dependency theory, this finding indicates that royal members who have a link with the external environment are more likely to have easy access to vital resources to aid in business performance improvement. Further analysis found that the big four international audit firms (AUQ) and AUQL positively moderate the relationship between royal ownership and firm performance. The finding suggests that AUQL and the big four international auditors play a complementary role in the governance system by strategising with royal members who own shares in the firm to further enhance firm performance. With the existence of royal family ownership, which is common amongst corporations in monarchy countries, the results of our study should help corporations in the GCC region to establish the best governance mechanisms to enhance firm performance.